1990
DOI: 10.1111/j.1432-1033.1990.tb19128.x
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and sequence analysis of the genes encoding the α and β subunits of the E1 component of the pyruvate dehydrogenase multienzyme complex of Bacillus stearothermophilus

Abstract: A 4175-bp EcoRI fragment of DNA that encodes the a and / 3 chains of the pyruvate dehydrogenase (lipoamide) component (El) of the pyruvate dehydrogenase multienzyme complex of Bacillus stearothermophilus has been cloned in Escherichia coli. Its nucleotide sequence was determined. Open reading frames (pdhA, pdhB) corresponding to the Ela subunit (368 amino acids, M , 41 312, without the initiating methionine residue) and E l p subunit (324 amino acids, M , 35 306, without the initiating methionine residue) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
34
0

Year Published

1992
1992
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 68 publications
2
34
0
Order By: Relevance
“…In additi on, the stretch of amino acids encoded by this exon and the contiguous phosphorylation site I is highly conserved both in length and in am ino acid homology when a comparison is made between the a -subunits from multiple species, both euka ryotic and prokaryotic, of the a -keto acid deh ydrogenase complexes (Fig. 6A) (10,26,(29)(30)(31)(32)(33)(34)(35)(36). Th e structure ofthis region is also intere sting.…”
Section: Variable Expression Of Pdc Defici Encymentioning
confidence: 99%
“…In additi on, the stretch of amino acids encoded by this exon and the contiguous phosphorylation site I is highly conserved both in length and in am ino acid homology when a comparison is made between the a -subunits from multiple species, both euka ryotic and prokaryotic, of the a -keto acid deh ydrogenase complexes (Fig. 6A) (10,26,(29)(30)(31)(32)(33)(34)(35)(36). Th e structure ofthis region is also intere sting.…”
Section: Variable Expression Of Pdc Defici Encymentioning
confidence: 99%
“…Three E1␣ BCDH peptide sequences from human (20), rat (72), and Pseudomonas putida (10) cells and the E1␣ subunit of the dual PDH/BCDH complex from B. stearothermophilus (26) were aligned to identify conserved regions that could serve as candidate sequences to design corresponding PCR primers. Several regions of extended resemblance (65) were chosen, and minimal homology requirements for PCR primer design were followed as previously discussed (19,23,56).…”
Section: Resultsmentioning
confidence: 99%
“…In these systems, it was found that the genes encoding the BCDH complex were clustered in an operon. The genes encoding the BCDH complex of P. putida (bkd genes) and the PDH/BCDH dual complex of B. subtilis and Bacillus stearothermophilus are clustered in the sequence E1␣, E1␤, E2, and E3 (10,11,26,27,59). Recently, the genes for the branchedchain fatty acid-specific BCDH from B. subtilis were cloned and sequenced (64).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It is not known whether the a and P subunits catalyze separate, partial reactions or whether af3 is the functional unit. Another possibility is that E1/3 plays a role in binding E1a to the E2 core (4,5), analogous to the role of protein X in anchoring E3 to the E2 core (6)(7)(8). Attempts to separate Ela and E113 with retention of enzymatic activity have been unsuccessful.…”
mentioning
confidence: 99%